Artemídia: um olhar sobre a arte contemporânea e suas relações sociais quando vista a partir do contexto do jogo - Melo, Venise Paschoal de (2017)
This thesis presents studies about contemporary art embedded in recent technologies, denominated as Media Art, and their possible relations with the game context. Based on a theoretical bibliographic research methodology, to understand and evidence in this trajectory, social interactions possibilities that occur during the spectator participation in this referred artistic proposition, we articulate, in interdisciplinary way, concepts and theories that involve art, technology and society. For this, from the observation of the artistic installations and theirs interaction forms, we identified and analyzed some parameters that contributed to the production of this association between art, game and sociability, so we look more closely at the openness circumstances of the art participation and their interaction to the subject, and to displacement of the Media Art to the urban centers were also seen; moreover, its vocation to interactivity was examined when mediated by technological artifacts, the reason that made us to perceive and consider a look of enchantment and fascination in certain participants, was also observed synesthesia as possibilities of expanding perceptions and stimulating feelings, as well as analyzed deeply the game contextual concepts. In this way, we explain about Media Art, their relation with technologies and aspects that with involve play, fun and entertainment, whose motivation ability was demonstrated both for social interactions and for the instigation of subjects' behavior changes. Therefore, we consider that the possible matches between the game and Media Art, including their forms of interaction and mediation, constitute in some kind of social transformation and sociality production.